MENINGKATKAN KEMANDIRIAN ANAK MELALUI METODE PEMBIASAAN DI PAUD KB MAWAR - Ade Sumarni; Alfian Ashidiqi Popyariyana (ADIBA : JOURNAL OF EDUCATION, 2025)
This study employs the Classroom Action Research (CAR) method to enhance the independence of children in PAUD KB Mawar. CAR is a reflective approach involving action participants, designed to improve rational capabilities in performing tasks and deepen understanding of the actions taken. It is conducted in four stages: planning, action implementation, observation, and reflection. The research subject is PAUD KB Mawar, with the object being the independence of 3-4-year-old children, totaling 10 children. Research instruments consist of observation and documentation instruments used to measure natural and social phenomena observed during CAR implementation. The findings indicate that learning at PAUD KB Mawar provides significant opportunities for educators to develop children's values, attitudes, knowledge, and skills. Before this research, daily activities felt monotonous, prompting educators to develop children's independence through habituation methods. Active teacher involvement plays a crucial role in observing and guiding children during habituation. CAR analysis reveals a significant improvement in children's independence. Initially, most children were unable to perform tasks such as tidying up toys, putting on shoes, and others. However, through well-executed habituation methods, children were able to achieve criteria for very good development in several aspects of independence. Supporting factors include the role of educators as role models, conducive environments, and continuous positive habituation. On the other hand, inhibiting factors involve parents' behaviors of overly pampering their children and being reluctant to leave them at school. This can delay the formation of children's independence From the research and observation results, it is concluded that habituation methods can eflectively enhance children's independence at PAUD KB Mawar. Despite inhibiting factors, consistent eflorts in providing positive habituation can overcome these obstacles.